Efeito agudo de diferentes protocolos de treinamento de força na concentração de lactato e no sinal eletromiográfico no exercício agachamento - Erica Fischer Fernandes Corradi (2011)
The duration of the repetition and the load intensity have influence in the acute and chronicle adaptation obtained from strength training. The back squat exercise has multi-joint characteristics and complex control in a manner that different possible adjustments may occur due to different training conditions imposed. The purposes of this study were: a) check the effect of different intensities and durations of repetition in integrated electromyographic signal of a protocol and between sets and between different strength training protocols; b) check the effect of different intensities and durations of repetition in integrated electromyographic signal between concentric and eccentric muscle actions in the series of different training protocols; c) check the effect of different intensities and durations of repetition in lactate concentration during and between strength training protocols. Nineteen men with recreational strength training experience, volunteered to this research. In the sessions 1 and 2, the volunteers have undergone tests of a one repetition maximum test (1RM) and familiarization of the duration of repetitions used in the study (4s and 6s) in the Smith machine back squat exercise. In the sessions 3 to 6, the volunteers have undergone tests of maximum volunteer isometric contraction (MVIC), and protocols of Smith machine back squat exercise, consisting of three sets of eight repetitions, with a three minute pause between the sets. In each training protocol, it was used an intensity and one duration of repetition controlled (protocols A 60%, 4s; B 60%, 6s; C 70%, 4s and D 70%, 6s). Blood samples were collected during rest and one minute after the 1st and 3rd set, to analyses of the blood lactate concentration. The integrated electromyographic signal of the concentric and eccentric actions of the vastus lateralis muscle (VL) was obtained through the average of repetitions of each set of the four training protocols. Increase in the blood lactate concentration was found throughout the exercises in all protocols (3rd > 1st > rest). Significant increase of the blood lactate concentration after the exercise was observed only when the intensity and duration of repetitions were simultaneously increased (protocol D > A). Throughout the sets there was an increase of iEMG in the eccentric muscle action only in the protocol with a longer duration of repetition and intensity (D) when comparing the 3rd with the 1st series, however, to the concentric muscle action, the 3rd set of the longer duration of repetition protocols presented higher iEMG than the 1st set of the respective protocol (B and D). The iEMG of the concentric muscle action was higher than the respective iEMG of the eccentric muscle actions in the longer duration repetition protocols (6s), apart from the training intensity (B and D). At last, when comparing the electromyographic activities of the concentric and eccentric actions among the four protocols, different responses were found, apart from the increase of the duration of repetition and/or training intensity. There was therefore, greater metabolic demand during exercise independent of training protocol and increased activation of concentric actions for the protocols of longer duration independent of intensity.